Factors affecting the recovery of COVID-19 patients in Pakistan, with a focus on smoking: A comprehensive analysis - Irfan, Muhammad; Akram, Waqar; Hooper, Vincent James (International Journal of Innovative Research and Scientific Studies, 2024)
This research paper delves into the various factors influencing the recovery of COVID-19 patients in Pakistan, with a specific emphasis on the impact of tobacco smoking. To unravel these connections, we conducted a data collection campaign employing a custom-designed questionnaire, gathering responses from 170 individuals who had successfully recovered from the coronavirus. Subsequently, we employed the Ordinary Least Squares (OLS) method to examine the influence of socio-economic factors on the recovery process. Our findings revealed that patients within the age range of 36 to 46 years exhibited an extended recovery period, requiring an additional three days for recuperation compared to their younger counterparts aged 17 to 25 years. Furthermore, patients aged above 46 years experienced a more prolonged recovery period, with a delay of up to seven days. Residence played a pivotal role in recovery times, as urban-dwelling patients showed a noteworthy advantage, recuperating 1.5 days sooner than their rural counterparts. A conspicuous relationship emerged regarding smoking habits, as patients who smoked tobacco required an additional two days for recovery when compared to non-smokers. Similarly, patients classified as obese experienced 2.6 more days to regain their health compared to individuals with a normal Body Mass Index (BMI). Remarkably, our analysis revealed that factors such as income, gender, and education were insignificant in terms of the number of the days required for recovery. These results provide a comprehensive understanding of the dynamics at play in the recovery process of COVID-19 patients in Pakistan, offering valuable insights for healthcare professionals and policymakers.